2012
DOI: 10.1186/1756-8722-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of unrelated atypical serum immunofixation patterns during Multiple Myeloma therapy

Abstract: Autologous stem cell transplantation (ASCT) is the gold standard therapy for suitable multiple myeloma (MM) patients after induction with high dose therapy. To date, the evidence of a reliable marker of prognosis in these cases remains scarce. Our aim was to evaluate appearance of unrelated atypical serum immunofixation patterns (ASIPs) as a marker of prognosis in MM patients submitted to ASCT. We retrospectively analysed data from 65 patients. Interestingly, we observed that presence of ASIPs was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The association of development of sMGUS with an improved outcome after allo-SCT, as demonstrated in this study, is consistent with several other reports that showed a better survival in MM patients with emergence of sMGUS after autologous SCT or chemotherapy. 1,2,4,6,9,10,[12][13][14]17 However, some studies did not observe a favorable outcome in patients with sMGUS. This may be related to differences in sample size, duration of follow up, technical and procedural variability, use of novel agents, and the percentage of patients that underwent autologous transplantation, or, as shown here, allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The association of development of sMGUS with an improved outcome after allo-SCT, as demonstrated in this study, is consistent with several other reports that showed a better survival in MM patients with emergence of sMGUS after autologous SCT or chemotherapy. 1,2,4,6,9,10,[12][13][14]17 However, some studies did not observe a favorable outcome in patients with sMGUS. This may be related to differences in sample size, duration of follow up, technical and procedural variability, use of novel agents, and the percentage of patients that underwent autologous transplantation, or, as shown here, allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Several terms have been used to describe this phenomenon, including abnormal protein band, oligoclonal protein bands, transient mono-or oligoclonal gammopathy, apparent isotype switch, oligoclonal humoral response, atypical serum immunofixation pattern, and in myeloma patients, as we will use in this study, secondary monoclonal gammopathy of undetermined significance MGUS (sMGUS). 18 We consider post-transplant MGUS as a subtype of sMGUS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They may be either multiple oligoclonal or single diffuse monoclonal protein bands on a diffuse polyclonal background on serum protein electrophoresis and therefore, difficult to interpret. Small APB are likely associated with improved depth of remission and possibly overall survival [1][2][3][4]. The presence of oligoclonality has been suggested to indicate longer progression-free survival and overall survival [4][5][6].…”
Section: Introductionmentioning
confidence: 99%